Effect of percentages of sand on the permeability of sandy clay - Bay, Dexter Zhiyang (2011)
Permeability is one of the important engineering parameters that affect a soil’s response to an applied loading. Soil in nature may be found as a mixture of fine and coarse grained material and it is difficult to measure permeability of such soils using the constant head or falling head permeability test. Also, these laboratory tests are unable to factor in pressure gradient onto the test subjects. Thus, the research focuses on the effect of the percentage of sand in a sandy clay mixture on the coefficient of permeability of that mixture using a Triaxial test. Pressure gradient, which translates to applied loading in real life situations, is also tested for its effects on the coefficient of permeability.